Visual design elements for data storytelling based on personality traits: a case of undergraduate students - Mohd Zanan, Muhammad Faris Basheer; Sheikh Abdul Aziz, Madihah (Asia Pacific University, 2023)
Prior studies found a strong correlation between a user's preference for information visualization and the variances in their personality. Visualization software have evolved recently and have given users a number of advantages. Although the usability aspects of visualization software have advanced significantly, they previously adopted a more general approach with their user interface and ignored user variations. There is a dearth of prior study examining user traits and preferred visual data storytelling elements. The use of individual variations as an adaptation metric in visualization tools has shown promise in overcoming the drawbacks of general approach from the user interface of visualization tools. This study intends to investigate into how users' preferences from the various visual design elements for storytelling relate to their personalities among university students in one institution. The study investigates whether personality affects user preferences for various visual design elements such as font type, font size, hierarchical, and comparative visualizations, which are extensively used in contemporary research and are associated with personality. To this end, a personality indicator will be performed to gauge each participant's personality. The participants will next answer a different series of questions on their preferences in visual design elements for data visualization and storytelling. This study may help to address the general issue with visualization tools and may suggest significant implications that may be used in the future design of visualization tools to improve the intuitiveness of the tool to suit various type of users, as well as for the visualization designers by choosing the best graphical visualizations for any given target audience to provide greater comprehension of the information in making critical decisions